Trend Kajian Kaedah Kontemporari Pembelajaran Al-Quran: Soroton Dari Tahun 2019 Hingga 2023 : Trends in the Study of Contemporary Methods of Quranic Learning: A Review from 2019 to 2023 - Nuril Ham Al Hafizah Zahari; Sharifah Norshah Bani Syed Bidin (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
This study examines recent developments in approaches to Qur’anic learning, which have evolved in response to contemporary circumstances and educational demands. Drawing on a literature review of articles published between 2019 and 2023, retrieved through a targeted search of the MyJurnal database, this research identifies a range of contemporary Qur’anic learning methods. The findings highlight numerous innovations and adaptations aimed at integrating traditional pedagogical techniques with modern educational needs and technologies. By illuminating current trends, this study not only contributes to ongoing discourse within the field of Qur’anic education but also provides educators and researchers with insights to further enhance the effectiveness of Qur’anic learning in the future.